School lunch nutritional adequacy: what is served, consumed and wasted. Issue 13 (13th September 2021) - Liz Martins, Margarida; Rodrigues, Sara SP; Cunha, Luís M; Rocha, Ada
Abstract: Objective: To determine nutritional adequacy of school lunch and to assess the impact of food waste on nutrient intake of primary schoolchildren. Design: The weighing method was used for evaluating initial servings and plate waste for lunch. Energy and nutritional contents of meals served, consumed and wasted were estimated using the software Food Processor Plus. The mean nutritional value of food served and consumed was compared with dietary guidelines. Setting: Portuguese public primary schools in the city of Porto. Participants: All 525 fourth-grade children, aged from 9 to 10 years old, attending to twenty-one public primary schools. Results: Overall, school lunches served did not meet the dietary guidelines for energy and nutrients, as only 12·5 % of the evaluated meals were adequate for energy, 33·5 % for proteins, 11·9 % for carbohydrates and 57·1 % for lipids. The majority of meals served were below the age-specific lower limit, namely for energy (83·7 %) and carbohydrates (86·8 %). The only exception, also unbalanced, was observed for proteins, as 42·4 % of lunches served exceeded the recommended upper limit. Furthermore, lunches served and consumed by children did not meet the dietary guidelines for fibre and for the micronutrients evaluated. Children wasted 26 % of the energy content provided in lunches, corresponding to 91·5 kcal, 25 % of proteins and 29 % of carbohydrates supplied. Conclusions: The lunches served and consumed by children at school canteens failed to meet nutritional standards. These results are not only a consequence of inadequate food portions served but also a result of the high plate waste values observed.